GASICA: generic automated stress induction and control application design of an application for controlling the stress state - van der Vijgh, Benny; Beun, Robbert J.; van Rood, Maarten; Werkhoven, Peter (Frontiers in Neuroscience, 2014)
1. In a multitude of research and therapy paradigms it is relevant to know, and desirably to control, the stress state of a patient or participant. Examples include research paradigms in which the stress state is the dependent or independent variable, or therapy paradigms where this state indicates the boundaries of the therapy. To our knowledge, no application currently exists that focuses specifically on the automated control of the stress state while at the same time being generic enough to be used in various therapy and research purposes. Therefore, we introduce GASICA, an application aimed at the automated control of the stress state in a multitude of therapy and research paradigms. The application consists of three components: a digital stressor game, a set of measurement devices and a feedback model. These three components form a closed loop (called a biocybernetic loop by Pope, Bogart, & Bartolome, 1995 and Fairclough, 2009) that continuously presents an acute psychological stressor, measures several physiological responses to this stressor, and adjusts the stressor intensity based on these measurements by means of the feedback model, hereby aiming to control the stress state. In this manner GASICA presents multidimensional and ecological valid stressors, whilst continuously in control of the form and intensity of the presented stressors, aiming at the automated control of the stress state. Furthermore, the application is designed as a modular open-source application to easily implement different therapy and research tasks using a high-level programming interface and configuration file, and allows for the addition of (existing) measurement equipment, making it usable for various paradigms.